Scientific Procedures of Complete and Incomplete Induction in the Methodology of Management Science - Lisiński, Marek (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The article presents the characteristics of the two basic scientific procedures used in management science. The procedures for complete induction and incomplete induction are presented from the perspective of the general methodology of science, the philosophy of science and the achievements of the methodology of management science. The analysis of these procedures specifically focuses on methods and techniques as well as on methodological directives relating them to the distinguished phases within the procedures of scientific research.